Targeting, Cascading, and Indirect Tax Design - Keen, Michael (IMF Working Papers; Working Paper ;, 2013)
This paper addresses two fundamental issues in indirect tax design. It first revisits the case for reduced rates on items especially important to the poor, establishing conditions under which even very crudely targeted spending measures better serve their interests. It then explores the welfare costs from cascading taxes, showing that these may actually be lower the wider the set of inputs that are taxed but, more to the point-and contrary to the common notion that 'a low rate on a broad base' is always good tax policy-may plausibly be large even at a low nominal tax rate and with few stages of production.